Karakter Pemimpin Kristen yang Ideal Menurut 1 Timotius 4:12 - Lindin Anderson; Trio Klaudius Kefas (Sekolah Tinggi Alkitab Batu, Malang, 2024)
This article focuses on explaining what the ideal character of a Christian leader looks like based on 1 Timothy 4:12. The book of 1 Timothy was chosen to describe the ideal character of a Christian leader because the Bible character Timothy is an ideal example in displaying the theological side of the character of a Christian leader. The background of this study is based on the fact that the theological values of the character of Christian leaders are increasingly fading and disappearing. This is characterized by a life centered on hedonism, which is dominantly displayed in life practices, the emergence of disputes between leaders, and various problems presented by church leaders. By taking a methodological approach to literature and exegesis on the text of 1 Timothy 4:12. So the results of the description in this study found that the ideal Christian leadership character from the perspective of the book of Timothy is honest, trustworthy, lives a holy life, and has a strong pastoral side that protects and builds the faith of the congregation. This side of the leadership character displayed by the figure of Timothy is a reflection and lesson for Christian leaders today. ABSTRAKTulisan ini berfokus menguraikan seperti apa karakter yang ideal sebagai seorang pemimpin Kristen dari kajian 1 Timotius 4:12. Kitab 1 Timotius dipilih untuk menguraikan keidealan karakter pemimpin Kristen, karena tokoh Alkitab Timotius merupakan percontohan yang ideal dalam menampilkan sisi karakter kepemimpin Kristen yang teologis. Latar-belakang kajian ini teruruai karena secara faktual makin memudarnya dan hilangnya nilai-nilai teologis karakter pemimpin Kristen saat ini. Hal ini ditandai dengan kehidupan yang berpusat pada hedonisme yang dominan ditampilkan dalam praktik kehidupan, menyeruaknya perselisihan kesesama pemimpin dan berbagai problematika yang ditampilkan para pemimpin gereja. Dengan melakukan pendekatan metologis literatur dan eksegesis pada teks 1 Timotius 4:12. Maka hasil uraian pada kajian ini menemukan, bahwa karakter kepemimpin Kristen yang ideal dari sudut pandang kitab Timotius adalah, jujur, amanah, hidup suci, serta kuat sisi pastoral yang mengayomi dan pembinaan iman jemaat. Sisi karakter kepemimpinan yang ditampilkan oleh figur Timotius ini menjadi refleksi dan pembelajaran bagi para pemimpin Kristen saat ini. Kata Kunci: Karakter, Pemimpin Kristen, Ideal, I Timotius 4:12